Early circulating tumor DNA dynamics as a pan‐tumor biomarker for long‐term clinical outcome in patients treated with durvalumab and tremelimumab. Issue 2 (13th December 2022) - Kansara, Maya; Bhardwaj, Neeru; Thavaneswaran, Subotheni; Xu, Chang; Lee, Jessica K.; Chang, Lo‐Bin; Madison, Russell W.; Lin, Frank; Hsu, Eugene; Patel, Vipul Kumar; Aleshin, Alexey; Oxnard, Geoffrey R.; et al.
Abstract : There is an urgent need to identify biomarkers of early response that can accurately predict the benefit of immune checkpoint inhibitors (ICI). Patients receiving durvalumab/tremelimumab had tumor samples sequenced before treatment (baseline) to identify variants for the design of a personalized circulating tumor (ctDNA) assay. ctDNA was assessed at baseline and at 4 and/or 8 weeks into treatment. Correlations between ctDNA changes to radiographic response and overall survival (OS) were made to assess potential clinical benefit. 35/40 patients (87.5%) had personalized ctDNA assays designed, and 29/35 (82.9%) had plasma available for baseline analysis, representing 16 unique solid tumor histologies. As early as 4 weeks after treatment, decline in ctDNA from baseline predicted improved OS ( P = 0.0144; HR = 9.98) and ctDNA changes on treatment‐supported and refined radiographic response calls. ctDNA clearance at any time through week 8 identified complete responders by a median lead time of 11.5 months ahead of radiographic imaging. ctDNA response monitoring is emerging as a dynamic, personalized biomarker method that may predict survival outcomes in patients with diverse solid tumor histologies, complementing and sometimes preceding standard‐of‐care imaging assessments. Abstract : We used a novel approach combining a tissue‐informed comprehensive genomic profiling assay with personalized blood‐based monitoring demonstrating that early ctDNA dynamics predict long‐term clinical outcomes in patients with different solid tumors treated with immune checkpoint inhibition. Molecular response as measured by ctDNA change from baseline represents an important emerging tool for assessing drug effect, complementary to imaging‐based response assessment.